2019
DOI: 10.1093/mnras/stz885
|View full text |Cite
|
Sign up to set email alerts
|

Opacity, variability, and kinematics of AGN jets

Abstract: Synchrotron self-absorption in active galactic nuclei (AGN) jets manifests itself as a time delay between flares observed at high and low radio frequencies. It is also responsible for the observing frequency dependent change in size and position of the apparent base of the jet, aka the core shift effect, detected with very long baseline interferometry (VLBI). We measure the time delays and the core shifts in 11 radio-loud AGN to estimate the speed of their jets without relying on multi-epoch VLBI kinematics an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…To address this problem, we could estimate the distance between the regions of the radio and gamma-ray emission production, taking the radio core opacity as the main source of the time lag (e.g. Kutkin et al 2019 ).…”
Section: Radio/gamma-ray Delay and Core Opacitymentioning
confidence: 99%
“…To address this problem, we could estimate the distance between the regions of the radio and gamma-ray emission production, taking the radio core opacity as the main source of the time lag (e.g. Kutkin et al 2019 ).…”
Section: Radio/gamma-ray Delay and Core Opacitymentioning
confidence: 99%
“…We estimate the component speed from the apparent speed of the jet features β app . Kutkin et al [32] showed that the jet speed, which is found by time delay of a flare when the observed frequency decreases, corresponds to the maximum β app estimated from the apparent motion of jet components. Therefore, we used the maximum value of β app = 15.31 for OJ 287 [33] to find β = 0.9979 assuming Γ min = (1 + β 2 app ) 1/2 .…”
Section: Connection Between Long-term Optical and Radio Flux Variabilitymentioning
confidence: 99%
“…If a source demonstrates flaring activity, it is possible to derive the kinematics of the jet innermost regions based on the measured core shift and multi-frequency time delays (Kudryavtseva et al 2011;Kutkin et al 2014Kutkin et al , 2018Kutkin et al , 2019. Assuming that the peak of a flare at a given frequency is observed when a moving jet feature passes through the region of the core at that frequency, it is possible to estimate the apparent projected speed of the component by comparing the light curve time delay, 𝑡, with the core shift for a pair of frequencies, 𝑟: 𝜇 app = 𝑟 / 𝑡.…”
Section: Agn Jets: Flares Speeds and Geometrymentioning
confidence: 99%
“…They were also used to constrain the spins of the supermassive black holes (Agarwal et al 2017) and the nature of the central engine (Zamaninasab et al 2014). If a source demonstrates flaring activity, it is possible to derive the jets innermost regions kinematics based on the measured core shift and multi-frequency time delays (Kudryavtseva et al 2011;Kutkin et al 2014Kutkin et al , 2018Kutkin et al , 2019Plavin et al 2019a). Differences in core positions should be taken into account for image registration when constructing the VLBI spectral index (e.g.…”
Section: Introductionmentioning
confidence: 99%